2013
DOI: 10.1128/jvi.01809-13
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of T Cell Responses during Acute and Latent Simian Varicella Virus Infections in Rhesus Macaques

Abstract: f Varicella zoster virus (VZV) is the etiological agent of varicella (chickenpox) and herpes zoster (HZ [shingles]). Clinical observations suggest that VZV-specific T cell immunity plays a more critical role than humoral immunity in the prevention of VZV reactivation and development of herpes zoster. Although numerous studies have characterized T cell responses directed against select VZV open reading frames (ORFs), a comprehensive analysis of the T cell response to the entire VZV genome has not yet been condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Our data also suggest that this is a selective recruiting of T cells since no B cells were detected at any time point. It is highly unlikely that these T cells are SVV specific given that SVV-specific T cell responses are not detected in the blood or BAL fluid until 7 dpi in this animal model (10,18,19). Similarly, VZV-specific T cells are also not detected in the blood until 3 days postrash (approximately 14 days after exposure) in children during primary infection (129).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data also suggest that this is a selective recruiting of T cells since no B cells were detected at any time point. It is highly unlikely that these T cells are SVV specific given that SVV-specific T cell responses are not detected in the blood or BAL fluid until 7 dpi in this animal model (10,18,19). Similarly, VZV-specific T cells are also not detected in the blood until 3 days postrash (approximately 14 days after exposure) in children during primary infection (129).…”
Section: Discussionmentioning
confidence: 99%
“…Animals were housed and handled in accordance with the guidance of the Oregon National Primate Research Center Institutional Animal Care and Use Committee. These animals were previously used to characterize specificity of the anti-SVV T cell response (18). Blood, bronchial alveolar lavage (BAL) fluid, and sensory ganglia were collected from all animals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular cytokine staining (ICS). PBMC and BAL cells were stimulated ex vivo with SVV lysate (1 g) or with an overlapping peptide pool representing ORFs 4, 11, 16, 31, and 37 (1 g) for 1 h followed by the addition of brefeldin A (Sigma, St. Louis, MO) for an additional 14 h. We have recently shown that all 5 ORFs are highly immunogenic during acute SVV infection, and the cumulative response accounts for 20% of the total acute T cell response (29). After incubation, cells were stained with antibodies directed against CD4 and CD8␤.…”
Section: Methodsmentioning
confidence: 99%
“…During latent infection, T cell responses were reduced significantly in magnitude and breadth compared to those observed during acute infection . Interestingly, T cell responses against ORF4, ORF11, ORF19, ORF31 and ORF 37 were maintained into latency, albeit at lower levels, whereas T cell responses to ORF10, ORF20, ORF29, ORF31, ORF62, ORF63 and ORF68 showed a significant decrease of about 83% between primary and latent infection . These observations may explain the success of the subunit vaccine HZ/su, which contains adjuvanted ORF68 protein and can potentially aid in the development of a multivalent subunit vaccine.…”
Section: Animal Models Of Vzv Studiesmentioning
confidence: 89%